Unmet Needs of Community-Residing Persons with Dementia and Their Informal Caregivers: Findings from the MIND at Home Study - Black, Betty S. (2013)
OBJECTIVES: To determine the prevalence and correlates of unmet needs in a sample of community-residing persons with dementia (PWD) and their informal caregivers. DESIGN: Analysis of cross-sectional, baseline participant characteristics prior to randomization in a care coordination intervention trial. SETTING: Baltimore, MD. PARTICIPANTS: Community-residing PWD (n=254) and their informal caregivers (n=246). MEASUREMENTS: In-home assessments of dementia-related needs based on the Johns Hopkins Dementia Care Needs Assessment. Bivariate and multivariate regression analyses were conducted to identify demographic, socioeconomic, clinical, functional and quality of life correlates of unmet needs. RESULTS: The mean number of unmet needs in PWD was 7.7 (SD=4.8) and 4.6 (SD=2.3) in caregivers, with almost all PWD (99%) and caregivers (97%) having one or more unmet needs. Unmet needs in PWD were significantly greater among those with higher cognitive function. Ninety percent of PWD had unmet safety needs, over half had unmet needs for meaningful activities, and almost one-third had not received a prior evaluation or diagnosis. Higher unmet needs in PWD were associated significantly with non-white race, lower incomes, less impairment in activities of daily living and more symptoms of depression. For caregivers, more than 85% had unmet needs for resource referrals and caregiver education. Higher unmet caregiver needs were associated significantly with non-white race, less education, and more symptoms of depression. CONCLUSION: Many community-residing PWD and their caregivers have unmet dementia-related needs for care, services and support. Providers should be aware that unmet needs may be higher among minority and low-income community residents, caregivers with lower education, and individuals with early-stage dementia. Identifying and treating symptoms of depression in PWD and caregivers may enable them to address their other unmet needs.